Perception of the Space of Bondage in the Poetic Works by A.I. Solzhenitsyn (Proceedings of Southern Federal University. Philology, 2021)
DOI 10.18522/1995-0640-2021-1-125-142The article examines the psychological situations in which A.I. Solzhenitsyn puts the lyric character of the poem “Dorozhenka” and poems in order to reflect the degree of his freedom and lack of freedom in the surrounding space. The perception of places of captivity is conveyed by the author not only through images of a prison cell, a prisoner transport vehicle, a prisoner train car, a barrack, a labor camp zone, but also through a generalization – the territory of the country surrounded by barbed wire. The space of enslavement appears in the form of concentric circles: the character himself is in the center, the next circle is a prison cell or a barrack, further is the GULAG zone and all of Russia, which is thought of as a large labor camp. The lack of freedom becomes the inner state of the lyric character, but at the same time it is aimed at achieving freedom of the spirit. According to Solzhenitsyn’s views, one can feel psychologically free only in the labor camp, having lost everything that is dear in ordinary life, and therefore losing fear, because, being out of prison, a person is crushed by suspicion and Stalin’s ideology, he is constantly under the threat of arrest.Keywords: space, lack of freedom, A. I. Solzhenitsyn, poems, the poem “Dorozhenka”.